The competency and service of tour guides affecting satisfaction of Muslim tourists - Tangkliang, Umaporn; Visuthismajarn, Parichart; Kongchouy, Noodchanath (Edelweiss Applied Science and Technology, 2025)
The study of how tour guide competence level and service quality have affected Muslim travelers’ satisfaction. The objectives of this study were: 1) to confirm the factors of tour guide competence and service quality that affect the satisfaction of Muslim travelers, and 2) to study how the aspect of tour guide competence affects the service quality and satisfaction level of Muslim travelers. A closed-ended questionnaire was used to gather information from 400 Muslim travelers who traveled with a leader guide. The outcomes were explored using the statistical packages SPSS and AMOS, with SEM used to analyze the demographic data. The proposed conceptual framework and hypotheses approach were used for evaluation. The first step was to estimate the general paradigm. Then, hypotheses were checked through measurement modeling. SEM was used to estimate the overall fit of the proposed model to verify the hypotheses. Subsequently, CFA was conducted. The results indicated that most of the respondents were male (55.75%), above 36 years old (49.75%), married (51.00%), had a bachelor's degree (50.25%), and were employees (31.00%). When considering the attributes and capacities of tour guides, it was found that skills (DE = .75), knowledge (DE = .24), ethics (DE = .12), and characteristics (DE = .07) were at a high level. The conclusion was that the structure and quality of guide services had a significant influence on tourist satisfaction. It was found that tour guide skills had a direct and positive influence on the level of service quality. In addition, service quality had a direct and positive influence on the level of tourist satisfaction, which would lead to repeat service use. Therefore, this study recommends that tour companies organize tour guide potential development training on the five pillars of Islam to meet the needs of Muslim tourists.